A study On Public Perception Towards Hydrogen Energy Acceptance In Sarawak - Olivia Trianna, Nathan (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aims to examine the public perception towards hydrogen energy acceptance in Sarawak. The variables that are brought into this study are behavioural intention, perceived ease of use, perceived usefulness, perceived behavioural control, social norms, attitudes and personal norms. The software SPSS Statistics version 26 are employed to determine the relationships between the dependent and independent variables with 311 targeted respondents who are residing in Sarawak. According to the findings, perceived ease of use, perceived usefulness, social norms and attitudes has a significant and positive relationship with behavioural intention meanwhile perceived behavioural control and personal norms is not significant towards behavioural intention. As a result, policymakers which includes government interventions is needed as well as to achieve the Sustainable Development Goals (SDGs). This is to encourage public to shift from conventional energy to hydrogen energy in Sarawak.